When Honi the Circle Maker meets Icarus: Periphery and Center in Y. H. Brenner’s In Winter and Shimon Adaf’s novel The Buried Heart - Schwartz, Yigal (MiKAN, 2021)
Based on a lecture given at the NAPH Conference at Stern College, Yeshiva University, New York, on 8 July, 2010. Shimon Adaf, one of Israel’s most outstanding and prominent young artists, has established in his writing a fascinating poetic strategy that Schwartz refers to as "self-creation of the center from within the periphery." The essence of this strategy, which is shared by other artists from the geo-socio-cultural periphery of Israel, is a seemingly voluntary gathering at the cultural margins into which they were forced in a move of demonstrative cultural insularity, and out of which they break into the "cultural center,” the most highly regarded cultural scene from which they have been excluded.